2010
DOI: 10.1021/om1005947
|View full text |Cite
|
Sign up to set email alerts
|

CpMn(CO)3-Catalyzed Photoconversion of Thiols into Disulfides and Dihydrogen

Abstract: The UV photolysis of CpMn(CO)3 with thiols at room temperature effected the following catalytic transformation: 2 RSH → R2S2 + H2. This reaction is a cleaner and greener way toward making disulfides, as it produces dihydrogen as the only side-product. The manganese system exhibits high chemoselectivity as the transformation proceeds efficiently even in the presence of numerous functional groups. A manganese dicarbonyl complex, CpMn(CO)2RSH, and cyclopentadiene have also been detected using FTIR and NMR spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
(16 reference statements)
3
11
0
Order By: Relevance
“…We have recently reported on the suitability of CpMn(CO) 3 as a precursor for a greener catalytic system: the conversion of thiols into disulfides with hydrogen as the only other product. 22 Although conditions for the transformation can be considered mild, the catalysis proceeds only in the absence of oxygen.…”
Section: ' Introductionmentioning
confidence: 99%
“…We have recently reported on the suitability of CpMn(CO) 3 as a precursor for a greener catalytic system: the conversion of thiols into disulfides with hydrogen as the only other product. 22 Although conditions for the transformation can be considered mild, the catalysis proceeds only in the absence of oxygen.…”
Section: ' Introductionmentioning
confidence: 99%
“…Our group has shown that thiols could be transformed into disulfides and H 2 using Mn(CO) 5 Br or CpMn(CO) 3 under UV-visible light. 9,10 Since enzymes such as glutathione reductase and cysteine reductase can easily reduce the respective disulfides into thiols using proton sources, combining the features of the manganese complexes and the enzymes into one may convert H + into H 2 without sacrificing thiols in the process through the reversible dissociation and formation of the S-S and S-H bonds.…”
mentioning
confidence: 99%
“…(2-(4-Hydroxyphenyl)disulfanyl)phenol18 (Table 2, entry 7).1 H NMR (500 MHz, CDCl 3 ) d 5.44 (s, 2H), 6.76 (d, J = 8.5 Hz, 4H), 7.34 (d, J = 8.5 Hz, 4H); 13 C NMR (125 MHz, CDCl 3 ) d 116.3 (4C), 128.6 (2C), 133.0 (4C), 156.2 (2C).2-(2-(2-Aminophenyl)disulfanyl)benzenamine 12b (Table2, entry 8). 1 H NMR (500 MHz, CDCl 3 ) d 4.22 (s, 4H), 6.59 (t, J = 7 Hz, 2H),6.71 (d, J = 8 Hz, 2H), 7.15 (t, J = 7 Hz, 4H); 13 C NMR (125 MHz, CDCl 3 ) d 115.3 (2C), 118.3 (2C), 118.8 (2C), 131.7 (2C), 136.9 (2C), 148.7 (2C).…”
mentioning
confidence: 99%